DEER KED, AN ECTOPARASITE OF MOOSE IN FINLAND: A BRIEF REVIEW OF ITS BIOLOGY AND INVASION - Kaitala, Arja; Kortet, Raine; Härkönen, Sauli; Laaksonen, Sauli; Härkönen, Laura; Kaunisto, Sirpa; Ylönen, Hannu (Lakehead University, 2009)
The deer ked (Lipoptena cervi) is an important ectoparasite of moose (Alces alces) that has rapidly invaded Finland during the last 50 years, and is currently found in southern parts of Finnish Lapland. We have studied the invasion, behavior, and ecology of this parasitic fly, and in this paper briefly review the effect of climate on the distribution of deer keds and our recent findings from host-choice experiments. The rapid increase of the deer ked is correlated with high moose densities in Finland. We propose that the availability of suitable hosts, not climate, is the primary factor affecting its northward range expansion. Our host-choice experiments indicated that deer keds are attracted by movement and large, dark objects. Our results suggest that this parasite may continue to spread northwards in the near future, and that its potential impact on cervids and human health warrants attention.